2015
DOI: 10.1039/c5dt00472a
|View full text |Cite
|
Sign up to set email alerts
|

Ru(EDTA) mediated partial reduction of O2 by H2S

Abstract: An effective procedure for selective reduction of O2 to H2O2 exploring the use of hydrogen sulfide, an obnoxious industrial pollutant as reductant is reported herein. The reduction of [Ru(III)(EDTA)pz](-) (EDTA(4-) = ethylenediaminetetraacetate; pz = pyrazine) by hydrogen sulfide resulting in the formation of a red [Ru(II)(EDTA)pz](2-) complex (λmax = 462 nm) has been studied spectrophotometrically and kinetically using both rapid scan and stopped-flow techniques. The time course of the reaction was followed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…[28,29] The use of hydrogen sulfide, an obnoxious industrial pollutant as an effective electron transfer agent in the reduction of [Ru III (edta)(pz)]has been reported quite recently. [30] Detailed kinetic and mechanistic studies of the reduction of [Ru III (edta)(pz)]to [Ru II (edta) (pz)] 2with hydrogen sulfide was performed strictly under argon atmosphere.…”
Section: -mentioning
confidence: 99%
See 3 more Smart Citations
“…[28,29] The use of hydrogen sulfide, an obnoxious industrial pollutant as an effective electron transfer agent in the reduction of [Ru III (edta)(pz)]has been reported quite recently. [30] Detailed kinetic and mechanistic studies of the reduction of [Ru III (edta)(pz)]to [Ru II (edta) (pz)] 2with hydrogen sulfide was performed strictly under argon atmosphere.…”
Section: -mentioning
confidence: 99%
“…It had been reported that the rate of reduction increased linearly with increasing concentration of HSat a constant pH (8.5). [30] The observed decrease in the rate of the reduction of [Ru III (edta)(pz)]at lower pH could be explained in terms of the lower reducing ability of hydrogen sulfide (which is the major reacting species at pH < 7.0) than its conjugate base HS -(pK 1 of H 2 S is 7.02). [31] Considering that HSis the predominant reacting species at pH 8.5, the overall experimental observations [30] can be accounted for in terms of the following reaction scheme (Scheme 6).…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the Ru III (edta) complex affords a range of stable and accessible oxidation states. Our recent research interests lie in studying the catalytic properties of Ru(edta)-type complexes toward oxidation of sulfur-containing molecules of biological importance [5][6][7][8]. Recently, we have shown that the Ru III (edta) complex can efficiently catalyze the oxidation of the thiocyanate ion (SCN − ) using H 2 O 2 as a precursor oxidant [9].…”
Section: Introductionmentioning
confidence: 99%